Practices related to late-onset sepsis in very low-birth weight preterm infants - Maria Regina Bentlin; Ligia M.S.S. Rugolo; Ligia S.L. Ferrari (Elsevier, 2015)
Objective: To understand the practices related to late-onset sepsis (LOS) in the centers of the Brazilian Neonatal Research Network, and to propose strategies to reduce the incidence of LOS. Methods: This was a cross-sectional descriptive multicenter study approved by the Ethics Committee. Three questionnaires regarding hand hygiene, vascular catheters, and diagnosis/treatment of LOS were sent to the coordinator of each center. The center with the lowest incidence of LOS was compared with the others. Results: All 16 centers answered the questionnaires. Regarding hand hygiene, 87% use chlorhexidine or 70% alcohol; alcohol gel is used in 100%; 80% use bedside dispensers (50% had one dispenser for every two beds); practical training occurs in 100% and theoretical training in 70% of the centers, and 37% train once a year. Catheters: 94% have a protocol, and 75% have a line insertion team. Diagnosis/treatment: complete blood count and blood culture are used in 100%, PCR in 87%, hematological scores in 75%; oxacillin and aminoglycosides is the empirical therapy in 50% of centers. Characteristics of the center with lowest incidence of LOS: stricter hand hygiene; catheter insertion and maintenance groups; use of blood culture, PCR, and hematological score for diagnosis; empirical therapy with oxacillin and aminoglycoside. Conclusion: The knowledge of the practices of each center allowed for the identification of aspects to be improved as a strategy to reduce LOS, including: alcohol gel use, hand hygiene training, implementation of catheter teams, and wise use of antibiotic therapy. Resumo: Objetivo: Conhecer as práticas relacionadas a sepse tardia (ST) nos centros da Rede Brasileira de Pesquisas Neonatais (RBPN) e propor estratégias para redução da ST. Métodos: Estudo transversal, multicêntrico da RBPN, aprovado pelo CEP. Três questionários sobre higienização das mãos, cateteres vasculares e diagnóstico/tratamento da ST foram elaborados e enviados aos coordenadores de cada centro. O centro com a menor incidência de ST foi comparado aos demais. Resultados: Todos os 16 centros responderam aos questionários. Quanto a higienização das mãos: 87% utilizam chlorhexidine ou álcool 70%; 100% álcool gel; almotolia/leito em 80% (50% dispõe de 1 dispensador para cada 2 leitos); Treinamento prático ocorre em 100%, teórico em 70% dos centros e 37% treinam 1 vez/ano. Cateteres: 94% tem protocolo para passagem, 75% grupo de inserção. Diagnóstico/tratamento: Hemograma e hemocultura são utilizados em 100% dos centros; PCR em 87%; 75% usam escores hematológicos; oxacilina e aminoglicosídeo são usados como terapia empírica em 50% dos centros. Características do centro com menor incidência de ST: rigorosa higienização das mãos; grupos de inserção e manutenção de cateteres; uso de hemocultura, PCR e escores hematológicos para diagnóstico da ST; tratamento empírico com oxacilina e aminoglicosídeo. Conclusões: O conhecimento das práticas de cada centro permitiu identificar aspectos a serem otimizados como estratégia para a redução da ST incluindo: uso de álcool gel, treinamento em higienização das mãos, implantação de grupos de cateteres e uso racional de antibióticos. Keywords: Sepsis, Newborn, Premature, Hand hygiene, Prevention and control, Palavras-chave: Sepse, Recém-nascido, Prematuro, Higiene das mãos, Prevenção & controle